PENGEMBANGAN E-LKPD MATERI TEKS NEGOSIASI PADA SISWA KELAS X SMA NEGERI 2 BINJAI - Amaliyah, Raudhatul; Naelofaria, Salmah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the development procedures, form, and feasibility of an Electronic Student Worksheet (E-LKPD) assisted by the PowerDirector application on negotiation text material for tenth-grade students. This research employed the Research and Development (R&D) method using the Borg and Gall development model, which was simplified into five stages: potential and problems, data collection, product design, design validation, and design revision. The research process began with needs analysis, followed by designing and developing the product in the form of an audiovisual E-LKPD, as well as validation by material experts, media experts, and assessment by a teacher. The results of the study indicate that: (1) the development of the E-LKPD was based on the need for interactive learning media that supports the achievement of learning outcomes and learning objectives in negotiation text material; (2) the E-LKPD was developed in an audiovisual form using the PowerDirector application with a duration of 4 minutes and 38 seconds, containing negotiation illustrations and Higher Order Thinking Skills (HOTS)-based questions; (3) the material expert validation result obtained an average score of 87.27% categorized as “very feasible,” the media expert validation result obtained an average score of 94.4% categorized as “very feasible,” and the teacher’s assessment obtained a score of 98% categorized as “very feasible.” Based on these results, it can be concluded that the E-LKPD assisted by the PowerDirector application on negotiation text material is valid and highly feasible to be used as a learning medium.